Local Public Finance: Three Essays on Accrual Accounting, Fiscal Rules and Corporatization - (:unkn) unknown (Freie Universität Berlin, 2023)
This dissertation consists of three independent empirical analyses which help to understand current approaches to increase efficiency across local governments and to stabilize their budgets. While Chapter 1 provides insights into the technicalities and effects of the accrual accounting reform on local budget figures, Chapter 2 evaluates the effectiveness of local government numerical fiscal rules. Chapter 3 gives an overview of local government corporatization and tests its potential drivers. In Chapter 1, I analyze the effects of the accrual accounting reform on the local government level. In particular, I am interested in the reaction of investment expenditure and revenue derived from asset sales to the aforementioned reform implementation. I exploit the cumulative reform trajectory of the local level in the German state Baden-Württemberg with the help of municipal microdata from the years 2005 to 2016. The identification strategy of this observational study is based on different matching techniques combined with the conditional Difference-in-Difference estimator. Results suggest a robust negative average treatment effect on reform municipalities’ investment expenditures for assets like buildings or roads. Results for revenues from asset sales remain weak but cautiously indicate a dampening effect for movable and financial assets. In Chapter 2 we investigate the impact of numerical fiscal rules on the aggregate local government budget deficit. Our focus lies on the balanced budget rule and we pay special attention to the role of rule design and transfer dependency. Using panel data covering 19 EU member states over a period of 19 years (1997-2015), we estimate a fiscal reaction function within a bias-corrected least square dummy variable (LSDVC) framework. Results suggest a discipline-enhancing effect of the balanced budget rule. Point estimates for related debt and expenditure rules remain insignificant. We can show that it is not the implementation of a plain rule that matters but rather its institutional design. Finally, within our empirical setting higher transfer dependency of local governments is related to higher aggregate budget deficits. In Chapter 3 we test several potential drivers of local government corporatization which is a widespread form of public service delivery outside the core administration. We use an index for corporatization intensity of 34 cities in the German state North Rhine-Westphalia over a period of 20 years (1998-2017). We collected the data for this index from 680 annual investment reports. The resulting panel dataset comprises more years than any other study in this field so far. In addition, we are able to disentangle corporatization to directly-owned companies from corporatization to first- and lower-tier subsidiaries. The results from a standard two-way fixed effects regression suggest that well-known drivers behave differently depending on the analyzed level of corporatization. Furthermore, point estimates indicate that corporatization intensity reacts to local fiscal hardship, the economic orientation of the mayor, and transparency-enhancing local government reforms. We show that increasing corporatization intensity over the past two decades was not based on the creation of additional directly-owned firms but rather on increasingly complex subsidiary structures.
Inaugural-Dissertation zur Erlangung des akademischen Grades eines Doktors der Wirtschaftswissenschaft des Fachbereichs Wirtschaftswissenschaft der Freien Universität Berlin